A Correction to the Paper ``On Α−Topological Vector Spaces’’ - Ram, Madhu (Science Journal of University of Zakho, 2019)
Theorem 3.30 in the published paper [1] is not correct. A valid reasoning concerning this error is given.
Keywords: α−open sets; α−topological vector spaces